1998
DOI: 10.1093/oxfordjournals.schbul.a033349
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Life of People With Schizophrenia in Boulder, Colorado, and Bologna, Italy

Abstract: The aim of the study was to compare the quality of life (QOL) and needs of people with schizophrenia in comprehensive treatment systems in two countries. One hundred people with schizophrenia and schizoaffective disorder were randomly selected from the caseload of a community mental health center in Boulder, Colorado, and 70 were similarly selected from public psychiatric treatment services in and around Bologna, Italy. Subjects were interviewed with QOL and needs assessment instruments and rated with the Brie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 16 publications
(16 reference statements)
0
41
0
1
Order By: Relevance
“…Bengtsson-Tops and Hansson (2001) found that the majority of individuals with mental illness were not satisfied with social relationships and stated a need for more social contacts in their daily life, more friends to visit their home and more people they could turn to if they had problems (see also Clinton et al, 1998). Warner et al (1998) commented that the family still meets many needs unmet by service provision and family living was associated with such advantages as greater residential stability, home ownership and social contact. De-institutionalization has resulted in a number of problems for the severely mentally ill (Simpson et al, 1989).…”
Section: Social Relationships Social Contact Mental Illness and Qolmentioning
confidence: 99%
“…Bengtsson-Tops and Hansson (2001) found that the majority of individuals with mental illness were not satisfied with social relationships and stated a need for more social contacts in their daily life, more friends to visit their home and more people they could turn to if they had problems (see also Clinton et al, 1998). Warner et al (1998) commented that the family still meets many needs unmet by service provision and family living was associated with such advantages as greater residential stability, home ownership and social contact. De-institutionalization has resulted in a number of problems for the severely mentally ill (Simpson et al, 1989).…”
Section: Social Relationships Social Contact Mental Illness and Qolmentioning
confidence: 99%
“…Evidence suggests that suicide rates in women are significantly higher than in men, and rural rates are more than three times higher than urban rates in China [25], in contrast to findings reported from Western countries [26]. In addition, multi-center studies have indicated that crosscultural or ethnic differences in schizophrenia with respect to SQOL also exist [27,28]. Thus, it is unlikely that findings of studies conducted with Caucasian patients could be generalizable to a non-Western culture such as that of Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…The reliability and validity of self-reported quality of life in persons with schizophrenia has been questioned since they are assumed to a various extent to suffer from neurocognitive deficits, disturbed thinking and communication [5], poor insight [6], downward adaptations of aspirations and affective, cognitive and reality distortion fallacies [7]. This discussion also refers to frequent empirical findings that objective external life conditions are only weakly associated with the subjective perception of quality of life [6,[8][9][10][11][12][13]]. An external assessment of quality of life has therefore been suggested as a complement to self-reported quality of life in individuals with a severe mental illness [14].…”
Section: Introductionmentioning
confidence: 99%